Rancang Bangun Prototipe Sistem Keamanan Akses Pintu menggunakan Radio Frequency Identification(RFID) Berbasis Internet of Things (Studi Kasus : PT Nok Indonesia) - Khumaidi, Ali; Pranoto, Setiadi Wiro (TRANSFORMASI, 2025)
Security is a crucial aspect in industrial environments, including at PT. NOK Indonesia, a company engaged in manufacturing. To ensure the safety of data, systems, and workers, an efficient and modern security system is essential. As technology advances, solutions such as Radio Frequency Identification (RFID) and the Internet of Things (IoT) have become increasingly adopted. RFID enables fast, reliable, and contactless identification, making it highly suitable for automatic door access systems. Currently, PT. NOK Indonesia still relies on a manual key system, which presents risks such as lost keys and inefficient access control. This study aims to design and develop a prototype of an automatic door access system using RFID sensors to enhance security. The research methods include observation, interviews, prototype development, and a series of tests, (such as speed response, solenoid function, buzzer response to registered and unregistered cards, testing with card protectors, and response distance measurements). The system was built using Arduino Uno, an RFID Reader, and programmed with Arduino IDE. Testing results show the system can read RFID cards in under 0.5 seconds and accurately log all access attempts. Integrating RFID and IoT improves both security and operational efficiency, replacing manual systems with a safer, more convenient, and reliable solution.